Immunological Issues in Recurrent Spontaneous Abortion - Nadia Ghasemi Darestani; Soheyla Hshemi; Zahra Rahimi; Raheleh Janghorbanianpoodeh (Journal of Medical Care Research and Review, 2024)
Recurrent spontaneous abortion (RSA) is a serious reproductive disorder of pregnancy that presents an unresolved issue in the fields of gynecology and obstetrics. RSA is usually defined as a woman suffering from ≥3 spontaneous abortions with the same sexual partner. The incidence rate of RSA ranges from 1 to 5% in women of childbearing age .[1]. The WHO defines recurrent pregnancy loss (RPL) as 3 or more consecutive pregnancy losses before the 20th week of pregnancy, while the American Society for Reproductive Medicine (ASRM) defines RPL after two pregnancy losses with clinical evidence of pregnancy (sonographic or histopathological evidence of pregnancy) [1,2]. About 1–5% of couples are affected by RPL, with significant consequences concerning their partnership and quality of life [3]. In the last years, the European Society of Reproduction and Embryology (ESHRE) [4], ASRM [5], German/Austrian/Swiss Society of Obstetrics and Gynecology (DGGG/OEGGG/SGGG) [6] and the Royal College of Obstetricians and Gynecologists (RCOG) [7] have developed guidelines to define a diagnostic and therapeutic work-up in RPL patients .Recent research has determined that the etiology of RSA is extremely varied, chiefly advanced high maternal age,inheritable genetic abnormalities, anatomical factors, infections, and endocrine dysfunctions .However, in most patients, the cause is unclear. Immune dysfunction accounts for more than half of these cases, and is usually referred to as immune-related RSA .A successful pregnancy requires an accurate immunologic dialogue at the maternal-fetal immune interface in the endometrium. [2] During early gestation, the occurrence of immunologic events over bilateral communication between the mother and fetus is extremely elaborate, and encompasses a great deal of immunocytes, including innate lymphocytes (ILC), macrophages, decidual dendritic cells (DCs), and T cells. These cells play a crucial role in establishing a balance between the inflammatory response and immune tolerance. [3]Existing evidence indicates that disorders occurring in the endometrial immune microenvironment are related to severe crucial reproductive disorders, which involve recurrent implantation failure (RIF) and RSA with inexplicable etiology. Innate Lymphoid Cells Innate lymphoid cells (ILCs) play significant roles in membrane immunity, tissue equilibrium, and metabolism regulation, and have inspired much research in recent years .[1-38]